Treating Intangible Inputs as Investment Goods : The Impact on Canadian GDP - Belhocine, Nazim (IMF Working Papers; Working Paper ;, 2009)
This paper constructs a data set to document firms' expenditures on an identifiable list of intangible items and examines the implications of treating intangible spending as an acquisition of final (investment) goods on GDP growth for Canada. It finds that investment in intangible capital by 2002 is almost as large as the investment in physical capital. This result is in line with similar findings for the U.S. and the U.K. Furthermore, the growth in GDP and labor productivity may be underestimated by as much as 0.1 percentage point per year during this same period.